Oscillating modes of driven colloids in overdamped systems - Johannes Berner (Nature Portfolio, 2018)
The motion of microparticles suspended in liquids is assumed to be dominated by viscous forces. Here, Berner et al. challenge this consensus by observing underdamped particle oscillations in a viscoelastic fluid and attributing it to the non-equilibrium fluctuations of liquid excited by particles.